Między modernizacją a zniewoleniem. Historiozoficzne implikacje konceptualizacji podziałów społecznych realnego socjalizmu - Brzechczyn, Krzysztof (Instytut Pamięci Narodowej, Oddział w Poznaniu, 2019)
The purpose of this chapter is to review and discuss conceptualizations of social divisions in real socialism. Namely, I will compare a neo-Marxist approach to social stratification with a neo-Weberian ones. The examples of the works made in Marxist tradition are concepts of Milovan Djilas and Michael Voslenski, whereas Leszek Nowak’s non-Marxian historical materialism can be interpreted as continuation of neo-Weberian tradition. This comparison will be made according to the following criteria: the position of party apparatus, the manner of explication, the status of political sphere and the vision of historical process. The compared concepts lead to different historiosophical and theoretical implications present in the empirical works which silently assumed a given approach. In the neo-Marxist approach, the very coming into existence of real socialism is discussed in terms of modernization processes, i.e. the necessity to ‘catch up with’ the historical delay of Central and Eastern Europe. In the version of neo-Weberian approach presented here, it is assumed that the basic interest of the political authorities is to gain domination over the rest of a society and that real socialism occurs as a result of the dominance of power over property in the societies of Eastern Europe.
Keywords: modernizacja; zniewolenie; realny socjalizm; nomenklatura; nowa klasa; Milovan Djilas; Leszek Nowak; nie-Marksowski materializm historyczny; klasa społeczna; komunizm